The Spread of Emphysematous Carbuncle in Cattle - I. Kh, Salimov; Z. Zh, Shapulatova; Sh., Khakimov; Zh. Kh., Kurbanov; R., Yuldoshev (European Journal of Life Safety and Stability (2660-9630), 2021)
The article presents the results of epizootic research carried out in dysfunctional farms on the emphysematous carbuncle of cattle, where mortality is often observed. The clinical signs of the disease are described. The results of pathologically examinations of dead animals are also presented. The causative agent of the disease was isolated, and it infected experimental animals, which showed clinical signs and pathological changes identical to the emphysematous carbuncle of cattle.